2008
DOI: 10.1097/01.nnd.0000300864.59997.27
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Training for Enhancing Psychiatric Nurses' Child Behavior Management Skills

Abstract: Management of behavior problems in an inpatient child and adolescent psychiatric unit is largely the responsibility of nurses, yet few evidence-based programs exist that prepare nurses for this role. A pilot study examined the effects of a 3-day standardized parent/teacher training program adapted for inpatient child and adolescent psychiatric unit nurses. Findings indicated that the standardized parent/teacher training program resulted in significant increases in self-reported use of child praise/incentives a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
1
8
0
1
Order By: Relevance
“…A further 21 studies in CYMH were excluded for one of three reasons: (a) they did not assess the effectiveness or efficiency of a KT strategy or intervention ( n = 11); (b) they assessed main outcomes other than behavioral or organizational ( n = 7); or (c) the stakeholders were the actual care users (i.e., youth or their caregivers; n = 3). Overall, 12 relevant reports were identified, five from community-based CYMH (Barwick, Peters, & Boydell, 2009; Henggeler, Shedow, Cunningham, Donohue, & Ford, 2008; Liddle et al, 2006; Homer et al, 2004; Tucker, Derscheid, Odegarden, & Olson, 2008) and seven from school-based CYMH (Atkins et al, 2008; Lerman, Vorndran, Addison, & Kuhn, 2004; Moore et al, 2002; Rohrback, Graham, & Hansen, 1993; Scott et al, 2005; Wallace, Doney, Mintz–Resudek, & Tarbox, 2004; Webster–Stratton, Reid, & Hammond, 2001) (see Table 2: Key study characteristics).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A further 21 studies in CYMH were excluded for one of three reasons: (a) they did not assess the effectiveness or efficiency of a KT strategy or intervention ( n = 11); (b) they assessed main outcomes other than behavioral or organizational ( n = 7); or (c) the stakeholders were the actual care users (i.e., youth or their caregivers; n = 3). Overall, 12 relevant reports were identified, five from community-based CYMH (Barwick, Peters, & Boydell, 2009; Henggeler, Shedow, Cunningham, Donohue, & Ford, 2008; Liddle et al, 2006; Homer et al, 2004; Tucker, Derscheid, Odegarden, & Olson, 2008) and seven from school-based CYMH (Atkins et al, 2008; Lerman, Vorndran, Addison, & Kuhn, 2004; Moore et al, 2002; Rohrback, Graham, & Hansen, 1993; Scott et al, 2005; Wallace, Doney, Mintz–Resudek, & Tarbox, 2004; Webster–Stratton, Reid, & Hammond, 2001) (see Table 2: Key study characteristics).…”
Section: Resultsmentioning
confidence: 99%
“…In a pilot study, Tucker et al (2008) evaluated the effects of a 3-day standardized parent/teacher training program aimed at improving interactions with children and adapted to meet the needs of registered child and adolescent psychiatric nurses ( n = 27). Nurses in Cohort 1 ( n = 12) were assigned to the intervention immediately and those in Cohort 2 ( n = 15) were assigned to wait list control group and scheduled for training one year later; assignment was based on availability and logistics.…”
Section: Resultsmentioning
confidence: 99%
“…The value of education and training in enhancing the knowledge, attitudes, confidence and competence of nurses has been acknowledged in the literature (Chan et al. 2008, Tucker et al. 2008).…”
Section: Discussionmentioning
confidence: 99%
“…2008). Tucker et al. (2008) recently demonstrated that a three day training workshop for child behaviour management led to significant improvements in psychiatric nurses’ knowledge and skills, with improved levels of empathy and a decreased tendency for negative judgement of parents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation